A PENGARUH HARGA, KUALITAS PRODUK DAN CITRA PERUSAHAAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PB 21 KOTA METRO: PENGARUH HARGA, KUALITAS PRODUK DAN CITRA PERUSAHAAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PB 21 KOTA METRO - Lystiawan; Febriyanto; Marhaban Sigalingging; Kuncoro Budi Riyanto (Universitas Muhammadiyah Metro, 2026)
The purpose of this study was to determine whether there is an influence of product quality, price, and company image on purchasing decisions of PB 21 Metro City consumers. This study uses a quantitative method by measuring research variables using an instrument in the form of a questionnaire given by PB 21 consumers in Metro City. The population of the study was all PB 21 consumers with samples taken using the probability sampling technique using the Cocran formula so that the number of samples found during the research period was 96 people. The questionnaire data that had been collected was then analyzed using the multiple linear regression formula. The results of the study showed that partially Product Quality influenced product purchasing decisions of consumers in PB 21 Metro City. The price variable had a negative effect on product purchasing decisions in PB 21 Metro City. Company image influenced purchasing decisions in PB 21 Metro City, and the variables of product quality, price, and company image simultaneously influenced purchasing decisions. This means that good product quality, accompanied by relatively affordable product prices and coming from shopping centers that are known to be cheap and complete, will provide a higher chance of purchasing decisions